Stability trends in carbocation intermediates stemming from germacrene A and hedycaryol - Tarannam, Naziha; Gupta, Prashant Kumar; Zev, Shani; Major, Dan Thomas (Beilstein Journal of Organic Chemistry, 2024)
In the current work, we analyzed the origin of difference in stabilities among the germacrene A and hedycaryol-derived carbocations. This study focused on twelve hydrocarbons derived from germacrene A and twelve from hedycaryol, which can be divided into three groups: four molecules containing 6-6 bicyclic rings, four 5-7 bicyclic compounds with the carbocation being on the seven-membered ring and the remaining four 5-7 bicyclic compounds with the carbocation on the five-membered ring. The variations in energy within the groups of carbocations (i.e., 6-6 and two kinds of 5-7 bicyclic carbocations) can be ascribed to intramolecular repulsion interactions, as seen from non-covalent interactions plots. Despite the structural similarities between germacrene A and hedycaryol cations, they possess a somewhat different stability trend. These differences are attributed to C+···OH intramolecular interactions present in some hedycaryol cations, which are absent in the carbocations derived from germecrene A.
Keywords: carbocation; germacrene A; hedycaryol; stability trend; terpenes